Taking sides : clashing views in crime and criminology - Hickey, Thomas J. [ (Thomas Joseph)] , 1953- (Contemporary learning series, 2012)
Presents controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. This title includes an issue summary, an issue introduction, and a postscript or challenge questions. It features an annotated listing of selected World Wide Web sites